Inferring bovine tuberculosis transmission between cattle and badgers via the environment and risk mapping - Chang, You; Hartemink, Nienke; Byrne, Andrew W.; Gormley, Eamonn; McGrath, Guy; Tratalos, Jamie A.; Breslin, Philip; More, Simon J.; de Jong, Mart C. M. (Frontiers in Veterinary Science, 2023)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is one of the most challenging and persistent One Health issues in many countries worldwide. In several countries, bTB control is complicated due to the presence of wildlife reservoirs of infection, i.e. European badger (Meles meles) in Ireland and the UK, which can transmit infection to cattle. However, a quantitative understanding of the role of cattle and badgers in bTB transmission is elusive, especially where there is spatial variation in relative density between badger and cattle. Moreover, as these two species have infrequent direct contacts, environmental transmission is likely to play a role, but the quantitative importance of the environment has not been assessed. Therefore, the objective of this study is to better understand bTB transmission between cattle and badgers via the environment in a spatially explicit context and to identify high-risk areas.We developed an environmental transmission model that incorporates both within-herd/territory transmission and between-species transmission, with the latter facilitated by badger territories overlapping with herd areas. Model parameters such as transmission rate parameters and the decay rate This is a provisional file, not the final typeset article parameter of M. bovis were estimated by maximum likelihood estimation, using the infection data from badger and cattle collected during a four-year badger vaccination trial. Our estimation showed that the environment can play an important role in the transmission of bTB, with a half-life of M. bovis in environment around 177 days. Based on the estimated transmission rate parameters, we calculate the basic reproduction ratio (R) within a herd, which reveals how relative badger density dictates the transmission. In addition, we simulated transmission in each small local area to generate a first between-herd R map that identifies high-risk areas.